(untitled) (Revista Electrónica REDINE, 2021)
Social expectations seek a new meaning to the performance of being a mother in time of COVID-19. The maternal essence becomes the corporeal transcendence to understand and understand the cultural demands, in the coexistence of the corporeality of being a doctor in times of uncertainty. This is a key category to start this essay, which has as its purpose a deep reflection from my maternal feelings and the documentary review. Where I seek to share experiences and concerns in this complex and intertwined perspectives in a process of reflection from the complexity of living together as a conglomeration of subjective interrelationships of being the mother of a doctor and a doctor who needs love in times of COVID-19